JKAP relates to disease risk, severity, and Th1 and Th17 differentiation in Parkinson's disease - Qingwei Yang (Wiley, 2021)
Abstract Objective JNK pathway‐associated phosphatase (JKAP) is previously reported to regulate immune/inflammatory process via T‐cell signaling, and closely involves in neurological diseases, while its implication in Parkinson's disease (PD) is unknown. Therefore, this study aimed to investigate the correlation of JKAP with Th1/Th2/Th17 cells and their clinical roles in PD patients, and then further explore the effect of JKAP on regulating CD4+ T‐cell differentiation in PD. Methods Totally 50 PD patients and 50 age‐/gender‐matched controls were enrolled. Their blood samples were collected and proposed to ELISA and flow cytometry assays for JKAP, Th1, Th2, and Th17 measurements. In vitro, CD4+ T cells were isolated from PD patients then transfected with JKAP overexpression and knockdown Lentivirus, followed by detection of markers (CD25+ cell proportion, CD69+ cell proportion, IFN‐γ, IL10, and IL17). Results JKAP was downregulated in PD patients compared to controls, which also showed good potency to discriminate them. Besides, JKAP negatively correlated with Th1 and Th17 cell proportions, but did not associate with Th2 cell proportion in PD patients; Interestingly, JKAP did not correlated with Th1, Th2, or Th17 cell proportions in controls. Furthermore, JKAP correlated with some parts of unified Parkinson’s Disease Rating Scale (UPDRS) and Mini‐Mental State Examination (MMSE) score. In vitro, JKAP overexpression repressed CD4+ T‐cell activation and its differentiation into Th1 and Th17 cells in PD, while JKAP knockdown appeared opposite effect. Interpretation JKAP associates with disease risk and severity, correlates with Th1 and Th17 cells, and regulates CD4+ T‐cell activation/differentiation in PD.